Assessment of Impact of Meteorology and Precursor in Long-term Trends of PM and Ozone in a Tropical City - Christian Mark G. Salvador; Angeles D. Alindajao; Karen B. Burdeos; Mark Anthony M. Lavapiez; Jhon Robin Yee; Angel T. Bautista; Preciosa Corazon B. Pabroa; Rey Y. Capangpangan (Aerosol and Air Quality Research)
Abstract Long-term trends of atmospheric pollutants, particularly ozone (O3) and particulate matter (PM) provide a direct evaluation of the response of the atmosphere to the environmental policies and the variability of anthropogenic and biogenic emissions. Here, we report the assessment of the temporal evolution of the air quality in a tropical urban city (Butuan) in the southern Philippines by evaluating the trends of meteorological conditions (i.e., temperature, R.H., boundary layer height), air pollutants (i.e., PM2.5, NO2, O3) and their precursors (Benzene, Toluene, and Xylene) from 2014 to 2020. During the seven-year measurement, the mean PM2.5 and PM10 mass concentrations were 8.7 ± 3.9 and 24.3 ± 12.0 µg m−3, with no single day exceeded the daily PM limit. The max concentrations of aerosol occurred during the dry season when the loss of particles through wet deposition was limited. Speciation of PM2.5 indicated that fine aerosol was dominated by sea salt and organic matter (OM). Analysis of the ratio of OM and sulfate indicated that the main source of pollution in the city was wildfire/biomass burning. The average O3 and NO2 mixing ratios during the same period were 22.3 ± 9.5 ppb and 8.1 ± 5.4 ppb while increasing at the rate of 0.409 ppb year−1 and 0.683 ppb year−1. The highest O3 concentration occurred during the summer months when photochemistry enhanced the formation of tropospheric O3. The increasing O3 trend was attributed to the contribution of anthropogenic VOCs (AVOCs), based on their ozone-forming potentials (OFPs). The seven-year measurement also showcased the variability of the atmospheric pollutants during the COVID-19 pandemic of 2020, when O3 substantially increased due to reduced vehicle transport activities. Overall, our results provide insights to better comprehend the sources of the variability of O3 and PM on a long-term temporal scale, as well as implications on relevant environmental policies in controlling air pollutants in a tropical developing region.